2012
DOI: 10.1159/000341106
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Practices in Aphasia Therapy in Finland: Challenges in Moving towards National Best Practice

Abstract: Aims: The objective of this article is to discover and document the state of clinical practices for aphasia therapy in Finland and to gather information for developing national best practice. Methods: Two surveys were administered in Finland that explored current clinical practices in aphasia rehabilitation and the resources available to speech and language therapists (SLTs). We integrated and compared the results of these surveys. The results are based on the responses of the 88 (45 + 43) returned questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…For now, only speech rehabilitation proved its efficacy on discourse recovery but the effect size of the positive studies is quite low (Brady et al, 2016;Yu et al, 2017). Nevertheless, the previous research found that the intensity of rehabilitation and the specialization of the therapist were more important than the rehabilitation technique used (Klippi et al, 2012). Therefore, there is an urgent need to develop new approaches to reduce aphasia in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…For now, only speech rehabilitation proved its efficacy on discourse recovery but the effect size of the positive studies is quite low (Brady et al, 2016;Yu et al, 2017). Nevertheless, the previous research found that the intensity of rehabilitation and the specialization of the therapist were more important than the rehabilitation technique used (Klippi et al, 2012). Therefore, there is an urgent need to develop new approaches to reduce aphasia in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…By and large, goals of speech and language intervention in Sweden still seem to primarily be based on formal tests of the patient's linguistic ability, and focus on the areas that the patient has particular difficulties with, as demonstrated by these tests. The same seems to be true also in other Nordic countries, for example Finland (Klippi, Sellman, Heikkinen and Laine 2012). The outcome of the intervention is mainly measured in terms of improved test results over time, and after a certain amount of intervention.…”
Section: Introductionmentioning
confidence: 82%
“…In recent years, approaches to aphasia treatment have broadened from traditional impairment-based language interventions to include approaches which focus on participation in communication activities and life roles; psychosocial well-being; and the impact of aphasia on significant others. Studies from around the world have shown that clinicians use an eclectic mix of aphasia treatment approaches often within an analytic model of treatment (Guo et al, 2014;Johansson, Carlsson, & Sonnander, 2011;Klippi, Sellman, Heikkinen, & Laine, 2012;Rose et al, 2014;Verna, Davidson, & Rose, 2009). However, in parallel with research outcome measurement, there is often a mismatch between the treatment approaches favoured by clinicians and the outcome measures used to gauge their effectiveness (Guo et al, 2014;Johansson et al, 2011;Klippi et al, 2012;Verna et al, 2009).…”
mentioning
confidence: 99%
“…The mismatch is further demonstrated by Klippi et al (2012) who conducted surveys with SLPs in Finland to examine aphasia clinical practices. In this study, 75% of respondents identified the primary aim of aphasia therapy to be the enhancement and improvement of everyday communication and interactional skills of the person with aphasia.…”
mentioning
confidence: 99%